Transverse field muon-spin rotation signature of the skyrmion lattice phase in Cu2OSeO3 - Lancaster, T; Williams, R; Thomas, I; Xiao, F; Pratt, F; Blundell, S; Hesjedal, T; Clark, S; Hatton, P; Hatnean, M; Keeble, D; Balakrishnan, G; et al. (American Physical Society, 2015)
We present the results of transverse field (TF) muon-spin rotation (μ+SR) measurements on Cu2OSeO3, which has a skyrmion-lattice (SL) phase. We measure the response of the TF μ+SR signal in that phase along with the surrounding ones, and suggest how the phases might be distinguished using the results of these measurements. Dipole field simulations support the conclusion that the muon is sensitive to the SL via the TF line shape and, based on this interpretation, our measurements suggest that the SL is quasistatic on a time scale τ>100 ns.